F17. EEG findings and seizure patterns in three infants with type 1 citrullinemia. (May 2018) - Rosengard, Jillian; Duberstein, Susan; Legatt, Alan D.
Abstract : Introduction: Citrullinemia is a urea cycle disorder which leads to toxic accumulation of ammonia and other metabolites. While it is widely accepted that citrullinemia is associated with seizures, there is no literature describing the typical EEG findings. Furthermore, there are no data available on long-term seizure outcomes. We report herein EEG findings and clinical courses in 3 patients with type 1 citrullinemia. Methods: We reviewed EEG records to identify patients with type 1 citrullinemia who had EEG studies at the Montefiore Medical Center. The EEG findings, clinical history and course in these patients were reviewed. Results: We identified 3 patients with type 1 citrullinemia with infantile onset of symptoms who had EEG studies. The initial EEG studies were done between 4 days and 3 weeks of life; all patients had subsequent follow-up EEGs. Patient 1 presented with abnormal movements and severe hyperammonemia (921  μ mol/L) at 3 weeks of life. EEG demonstrated independent left and right central electrographic and electroclinical seizures. She received emergent dialysis, lorazepam, levetiracetam, sodium phenylacetate and sodium benzoate. She had no further seizures, and at last follow-up at age 9 months, she was seizure-free off all anti-epileptic drugs (AEDs), on dietary modification and treatment with glycerol phenylbutyrate. Patient 2 presented on day 4 of life with lethargy and poor feeding. She suffered a cardiac arrest and was found to have severe hyperammonemia (>2000  μ mol/L). EEG demonstrated many independent left and right temporal electrographic seizures requiring phenobarbital boluses and midazolam infusion. She had no further seizures and was tapered off of phenobarbital at 6 months of age. She remains on dietary modification and treatment with arginine and sodium phenylbutyrate. Patient 3 presented with neonatal seizures. An EEG performed on day 7 of life demonstrated independent left and right central electrographic seizures. She was initially treated with levetiracetam, phenobarbital, and hemodialysis. She is now 10 years old and has been seizure-free for 3 years. She is currently on levetiracetam, dietary modification and treatment with arginine and sodium phenylbutyrate. Conclusion: Our 3 patients with type 1 citrullinemia all presented in the neonatal period with independent electrographic seizures in homologous regions in both hemispheres. One patient also had bilateral independent electroclinical seizures. Our findings suggest that bilateral independent electrographic seizures are a characteristic EEG finding in neonatal-onset type 1 citrullinemia. Two of our patients had no further seizures after the initial presentation and are now off AEDs. The third patient has been seizure-free for 3 years on levetiracetam as the only AED. These findings suggest that patients with citrullinemia may not have further seizures once their metabolic state is controlled and, therefore, may not require long-term AEDs.